Differences and Temporal Changes in Risk of Invasive Pneumococcal Disease in Adults with Hematological Malignancies: Results from a Nationwide 16-Year Cohort Study. (28th May 2020) - Andersen, Michael Asger; Niemann, Carsten Utoft; Rostgaard, Klaus; Dalby, Tine; Sørrig, Rasmus; Weinberger, Daniel M; Hjalgrim, Henrik; Harboe, Zitta Barrella
Abstract: Background: Patients with hematological malignancies (HM) are known to carry an increased risk of invasive pneumococcal disease (IPD). However, temporal variations in IPD risks following a cancer diagnosis remain poorly characterized. To inform vaccine guidelines and patient management, we assessed the IPD incidence among patients with HM and other malignancies. Methods: The study population included all individuals aged ≥15 years during 2000–2016 in Denmark. Variations in incidences of IPD over time and between different types of hematological malignancies and diagnoses were assessed by Poisson regression. Results: During 85 002 224 person-years of observation, 13 332 episodes of a first IPD were observed, of which 765 (5.7%) occurred among individuals with HM. Among HM patients, the IPD incidence rate decreased continuously during the study period (rate ratio per year, 0.91; 95% confidence interval, .90–.92). The risk of IPD in patients with HM was up to 39 times higher when compared to the background population and was highest for multiple myeloma, acute lymphoblastic leukemia, and chronic lymphocytic leukemia. Unlike other malignancies, the increased IPD risk did not wane with the time since HM diagnosis. We found a vaccination uptake of only ≤2% in patients with HM and ≤1% for those with other types of malignancies. Conclusions: Adults with HM in general and patients with lymphoid malignancies in particular have an increased risk for IPD, compared with patients with other types of cancer and with individuals free of cancer. The pneumococcal vaccination uptake is extremely low in this at risk-population. Efforts to prevent IPD in HM patients are continuously warranted. Abstract : The risk of invasive pneumococcal disease (IPD) is nearly 40 times higher in adults with hematological malignancies, especially those with lymphoid malignancies. Given the high IPD risk, efforts to prevent IPD in hematological malignancies patients are continuously warranted.